NILAI-NILAI KEARIFAN LOKAL DALAM TARI ENDENG ENDENG SUKU BATAK MANDAILING: KAJIAN PENDIDIKAN KARAKTER - Asri Yulianda; Anna Leli Harahap; Shopiah Anggraini Rambe (Jurnal Education and Development, 2023)
This study aims to describe the value of local wisdom contained in the oral tradition of the Mandailing community. The research method used is descriptive analysis method with the data source in the study is the endeng endeng dance. The results showed that there were 3 values ​​of local wisdom, namely manners, life advice, social procedures. The results also show that oral traditions have local wisdom values ​​that need to be revitalized to be applied and taught to the younger generation now as the basis for character building.